2000
DOI: 10.1097/00007632-200010150-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Multicenter Clinical Evaluation of an Anterior Cervical Fusion Cage

Abstract: These results demonstrate that outcomes after a cervical fusion procedure with a threaded cage are the same as those of a conventional uninstrumented bone-only anterior discectomy and fusion with a low risk of complications and rare need for autogenous bone graft harvest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
205
3
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(232 citation statements)
references
References 20 publications
12
205
3
12
Order By: Relevance
“…In a multicenter study [11] comparing the cylindrical cage with non-instrumented boneonly fusion, similar success rates were shown for the two techniques. Overall complication rate for the cage is lower.…”
Section: Discussionmentioning
confidence: 67%
“…In a multicenter study [11] comparing the cylindrical cage with non-instrumented boneonly fusion, similar success rates were shown for the two techniques. Overall complication rate for the cage is lower.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, graft material as soft as cancellous bone can be used. Cancellous bone can be obtained with less morbidity and incorporates more quickly than allograft [14]. This may account for the findings that a higher percentage of levels were found fused in the cervical cage group at 3 months, though this difference was not detectable at later follow-ups.…”
Section: Rationale For Carbon Fiber Cagesmentioning
confidence: 97%
“…To avoid donor site complications altogether, empty carbon fiber osteoconductive polymer cages were placed by Payer et al [18], who reported segmental stability in all 25 patients and bone fusion in 24. Hacker et al [14] reported nearly 100% fusion rates with threaded carbon fiber cages and autograft versus 90% for non-instrumented bone graft alone. Salame et al [19] reported 98% fusion in 100 patients with the I/ F carbon cage.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Anterior cervical spine surgery-associated complications in a retrospective case-control study an overstatement that anterior cervical approach constitutes one of the most rewarding spinal procedures (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Review Articlementioning
confidence: 99%